Patient satisfaction concerning implant-supported prostheses: an observational study - GURGEL,Bruno César de Vasconcelos (2015)
The aim of this observational study was to assess the degree of patient satisfaction toward implant-supported prostheses. A questionnaire was used with two scales (one consisting of detailed adjectival and the other of numerical responses) regarding chewing, esthetics, speaking, comfort and overall satisfaction. The scales were administered to a sample of 147 patients treated with implants and prostheses. The data were submitted to the Kappa statistic and the Chi-square test to analyze the association between dependent and independent variables. High degrees of satisfaction (greater than 91%) were found for all categories evaluated, regardless of gender, age, number of implants or type of prosthesis. “Comfort” was associated significantly with the number of implants (p = 0.038), and “speaking” was associated significantly with the type of prosthesis (p = 0.029). Positive agreement was found between the scales for all categories evaluated, without statistically significant differences regarding respondent preference (p = 0.735). Patients treated with implant-supported prostheses were highly satisfied with the treatment.